2008
DOI: 10.1016/j.postcomstud.2008.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Contextual effects on historical memory: Soviet nostalgia among post-Soviet adolescents

Abstract: Using an original survey of adolescents in post-communist Russia and Ukraine, this study analyzes attitudes toward the dissolution of the Soviet Union. The results demonstrate how contextual factors – the republic's position within the former Soviet Union and prior history of colonization – affect the level of nostalgia among the young generation. Based upon semi-structured interviews with adolescents, the study identifies sources of positive and negative attitudes toward the Soviet demise. Furthermore, the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 16 publications
1
12
0
1
Order By: Relevance
“…Even so, people yearn for the past—in Poland as in other postsocialist countries (Boyer, ; Cernat, ; Nikolayenko, ; Pobłocki, ; Todorova & Gille, ). A survey study carried out in three large regions of Poland in 2003 revealed that over 50% of the sample evaluated various aspects of their life before 1989 as “better than now.” According to the Social Diagnosis, a biannual survey carried out on large, representative national samples (Czapiński & Panek, ), over 60% of the people surveyed in 2000 reported that their lives before 1989 were better.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Even so, people yearn for the past—in Poland as in other postsocialist countries (Boyer, ; Cernat, ; Nikolayenko, ; Pobłocki, ; Todorova & Gille, ). A survey study carried out in three large regions of Poland in 2003 revealed that over 50% of the sample evaluated various aspects of their life before 1989 as “better than now.” According to the Social Diagnosis, a biannual survey carried out on large, representative national samples (Czapiński & Panek, ), over 60% of the people surveyed in 2000 reported that their lives before 1989 were better.…”
mentioning
confidence: 99%
“…Postcommunist nostalgia has been treated by cultural anthropologists, sociologists, political scientists, and literature critics (Bartmanski, ; Boyer, ; Boym, ; Ekman & Linde, ; Pobłocki, ; Todorova, & Gille, 2010), as well as in quantitative research (Cernat, ; Ekman, & Linde, 2005; Nikolayenko, ; Strzeszewski, ). In the introduction to a book devoted entirely to this phenomenon, Todorova () ironically commented “A spectre is haunting the world of academia: the study of post‐Communist nostalgia” (p. 1), suggesting that this “elusive” concept has attracted too much attention from researchers from different fields.…”
mentioning
confidence: 99%
“…However, when they began independently to form their own interpretations of the past and to erect their monuments in significant sites of Soviet repression, their paths increasingly began to diverge. Although the framing of their interpretations of the past was fixed by the mid-1990s, over time one dominant visual narrative has emerged, and today, we argue, one visual language of memorialisation has taken precedence, with implications not only for how the Gulag period is remembered in Russia, but also for the contested contemporary interpretations of the Soviet and particularly the Stalin eras (Shlapentokh and Bondartsova 2009;Oushakine 2007;Nikolayenko 2008). These commemorations take place in the absence of any 'official' state public commemoration policy for the repressions.…”
Section: Introductionmentioning
confidence: 83%
“…Past ethnological studies have indicated societal occurrences of collective nostalgia that triggered within‐group unity, support, and motivation, as well as outgroup division, dislike, and/or violence in Kashmir (Bhan & Trisal ), Eastern Europe (Volčič ; Nikolayneko ; Goulding & Domic ), and Western Europe (Mols & Jetten ; Smeekes et al ). Collective nostalgia has also been observed to reshape collective memories (Farrar ; Mols & Jetten ) that caused a paradoxical wish that habitants wanted to return to pasts known for exploitation and oppression in Zanzibar (Bissell ) and South Africa (Coullie ).…”
Section: Nostalgic Research Survey Past 2000mentioning
confidence: 99%